Divergence, gene flow, and speciation in eight lineages of trans‐Beringian birds. Issue 18 (2nd September 2020) - McLaughlin, Jessica F.; Faircloth, Brant C.; Glenn, Travis C.; Winker, Kevin
Abstract: Determining how genetic diversity is structured between populations that span the divergence continuum from populations to biological species is key to understanding the generation and maintenance of biodiversity. We investigated genetic divergence and gene flow in eight lineages of birds with a trans‐Beringian distribution, where Asian and North American populations have likely been split and reunited through multiple Pleistocene glacial cycles. Our study transects the speciation process, including eight pairwise comparisons in three orders (ducks, shorebirds and passerines) at population, subspecies and species levels. Using ultraconserved elements (UCEs), we found that these lineages represent conditions from slightly differentiated populations to full biological species. Although allopatric speciation is considered the predominant mode of divergence in birds, all of our best divergence models included gene flow, supporting speciation with gene flow as the predominant mode in Beringia. In our eight lineages, three were best described by a split‐migration model (divergence with gene flow), three best fit a secondary contact scenario (isolation followed by gene flow), and two showed support for both models. The lineages were not evenly distributed across a divergence space defined by gene flow ( M ) and differentiation ( F ST ), instead forming two discontinuous groups: one with relatively shallow divergence, no fixed single nucleotide polymorphisms (SNPs), and high rates of gene flow between populations; and the second with relatively deeply divergent lineages, multiple fixed SNPs, and low gene flow. Our results highlight the important role that gene flow plays in avian divergence in Beringia.